Impact of CYP3A4*18 and CYP3A5*3 Polymorphisms on Imatinib Mesylate Response Among Chronic Myeloid Leukemia Patients in Malaysia. Issue 2 (December 2016) - Maddin, Najlaa; Husin, Azlan; Gan, Siew; Aziz, Baba; Ankathil, Ravindran
Abstract Introduction Imatinib mesylate (IM), a selective inhibitor of the BCR-ABL tyrosine kinase, is a well-established first-line treatment for chronic myeloid leukemia (CML). IM is metabolized mainly by cytochrome P450 (CYP) in the liver, specifically the CYP3A4 and CYP3A5 enzymes. Polymorphisms in these genes can alter the enzyme activity of IM and may affect its response. In this study, the impact of two single-nucleotide polymorphisms (SNPs), CYP3A5*3 (6986A>G) andCYP3A4*18 (878T>C), on IM treatment response in CML patients (n  = 270; 139 IM resistant and 131 IM good responders) was investigated. Methods Genotyping ofCYP3A4*18 andCYP3A5*3 was performed using the polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) technique. The association between allelic variants and treatment response was assessed by means of odds ratio (OR) with 95% confidence intervals calculated by logistic regression. Results Our results indicated that CML patients carrying the heterozygous (AG) and homozygous variant (GG) genotype ofCYP3A5 *3 were associated with a significantly lower risk of acquiring resistance with OR 0.171; 95% CI: 0.090–0.324, p  < 0.001 and OR 0.257; 95% CI: 0.126–0.525, p  < 0.001, respectively. Although CML patients carrying the heterozygous (TC) genotype ofCYP3A4*18 showed a lower risk of acquiring resistance toward IM (OR 0.648; 95% CI: 0.277–1.515), the association was not statistically significant (p  = 0.316). No homozygous variant (CC) genotype ofCYP3A4*18 was detected among the CML patients. Conclusion It is concluded that polymorphism ofCYP3A5*3 is associated with IM treatment response in Malaysian CML patients with carriers ofCYP3A5*1/*3 andCYP3A5*3/*3 genotypes posing lower risk for development of resistance to IM.